Integration of automation resources in holonic manufacturing applications - Leitão, Paulo (2010)
Holonic and agent-based paradigms are very suitable in the development of distributed manufacturing control systems, taking advantage of their modularity, decentralization, and ability to support dynamic and complex system design features. However, the integration of manufacturing resources within the holonic manufacturing control applications remains a problem, because no efficient standard allows an easy, transparent and essentially independent integration. This paper proposes an integration process that allows the integration of automation resources independently from the holonic control application, using some concepts derived from the Manufacturing Message Specification (MMS) application protocol and implemented over a distributed object platform.